Opening words - Aksela, Maija (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
The symposium starts with opening words given by the chair of the event, Professor Maija Aksela from University of Helsinki, Finland. This is a farewell symposium for Professor Aksela as the Director of LUMAT Science Research Forum. She built the LUMAT Symposium 15 years ago. Read more here. Program 13.00–13.10 Opening words Maija Aksela University of Helsinki, Finland 13.10–13.30 Threads and Strings: Interweaving Bhutanese traditional music, textiles and STEM Som Gurung, Tshering Dorji, Johan Westman, Tashi Wangmo and Thinley Phuntsho Paro college of educaion (HEDPC and STEM), Bhutan 13.30–13.50 A Case Study of Integrating Non-formal Learning for Developing Teaching Resources for Sustainability During a Science Teacher Education Course Safwatun Nida Universitas Negeri Malang, Indonesia 13.50–14.10 Development of a Regional STEM Education Ecosystem in the Lower Mekong Basin: A Case Study of the Faculty of Science, Nakhon Phanom University, Thailand Wuttichai Gunnula, Patchalai Anuchaiwong, Wissarut Srivarom, Pharit Kamsri, Natchanun Painetr and Cherdchai Phosri Faculty of Science, Nakhon Phanom University, Thailand 14.10–14.25 Break 14.25–14.45 Engaging learners in non-formal Science Technology Engineering and Mathematics education: ESKOM EXPO for Young Scientists Nalini Dookie and Angela James University of KwaZulu-Natal, South Africa 14.45–15.05 Integrative Educational Projects and Teacher Practice: An Analytic Study Suraya Ayyad, Eman Zaitoun, Samar Nazzal, and Asma Zaitoun Innovation for Creativity Development Association (ICDA), Jordan 15.05–15.25 Engaging Science Learners at Disadvantaged schools in South Africa in the Use of Culturally-Anchored Virtual Reality Simulations for Inquiry-based Learning Umesh Ramnarain, Mafor Penn and Noluthando Mdlalose University of Johannesburg, South Africa 15.25–15.40 Break 15.40–16.00 Computational Drug Design in Problem-Based Learning: A Pedagogical Experience in Pre-Service Chemistry Teachers Jorge Rodríguez-Becerra Universidad Tecnológica Metropolitana, Escuela de Postgrado, Santiago, Chile. José Hernández-Ramos Centro de Investigación Avanzada en Educación, Instituto de Educación, Universidad de Chile, Periodista José, Santiago, Chile. Lizethly Cáceres-Jensen and Sofía Druker Ibáñez Universidad Metropolitana de Ciencias de la Educación, Departamento de Química; Physical & Analytical Chemistry Laboratory (PachemLab), Facultad de Ciencias Básicas, Santiago, Chile. 16.00–16.20 Co-designing Science Clubs for Non-formal STE(A)M Learning Environments through Design-based Research Maija Aksela and Outi Haatainen LUMAlab Gadolin, University of Helsinki, Finland 16.20–16.30 Closing words Maija Aksela University of Helsinki, Finland